Pengaruh Person Job-Fit dan Job Burnout terhadap Kepuasan Kerja Gen Z (Studi Pada Pengikut Akun Twitter Worksfess) - Yulianto, Wahyu; Nusannas, Iman Sidik; Safinatunnajah, Salma (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This research was conducted to find out how the influence of Person Job Fitand Job Burnout variables on Gen Z Job Satisfaction. In this study, Person Job Fitand Job Burnout variables were independent variables and job satisfaction was thedependent variable. Primary data collection using simple random samplingtechnique as a sample, with a total of 80 gen z respondents as followers of theWorksfess Twitter account who had resigned. The data analysis method used in thisstudy is multiple linear regression with the help of data processing using SPSSsoftware. Based on the results of the research that has been done, it shows thatsimultaneously the independent variables have a positive and significant influenceon the dependent variable (job satisfaction). And the value of r square shows thenumber 68.1% which means that all independent variables have a simultaneouseffect of 68.1%.Keywords: Person Job Fit, Job Burnout, and Job Satisfaction